Kontribusi Pekerja Wanita terhadap Pendapatan Keluarga Petani di Desa Banyu Hirang Kecamatan Gambut Kabupaten Banjar - Rizki Purnama; Dessy Maulina (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to measure the contribution of women workers to family income of farmers in Banyu Hirang Village, Gambut District, Banjar Regency. The scope of the research is the contribution of women to family income in Banyu Hirang Village, Gambut District, Banjar Regency. The type of research used in Banyu Hirang Village is quantitative research where quantitative data and objective statistical measurements are carried out through scientific calculations from a sample of Banyu Hirang Village residents who answer survey questions that have been prepared to determine the frequency and percentage of their responses.The result of this research is that the involvement of the respondent's contribution to the total family income is 48.7%. So, the contribution of housewives who work as farmers in Banyu Hirang Village, Gambut District is stated to be quite contributing. This means that the contribution made by housewives who work as farmers in Banyu Hirang Village, Gambut District has fully helped meet family income.